(untitled) (Biological Sciences - PJSIR, 2010)
Antifungal activity of crude solvent and aqueous extracts of the medicinal plant, Trianthema pentendra Linn., against the dermatophytic fungi, Aspergillus niger, Aspergillus flavus, Paecilomyces varioti, Microsporum gypseum and Trichophyton rubrum revealed that ethanol and aqueous extracts were the most effective antifungal agents as compared to methanol, chloroform and ethyl acetate extracts. Some basic elements, Al, Ca, Cu, Fe, Mg, Mn, P, S and Zn were also determined in the medicinal plant, T. pentendra, using atomic absorption spectrophotometry and U.V spectrophotometry. T. pentendra contained considerable amount of elements which have therapeutic effects in skin diseases.